The Effect of Sulfate Exposure on The Mechanical Properties of Conventional Portland Composite Cement Concrete - Masrafat, Hazen; Sutrisno, Wahyuniarsih; Tajunnisa, Yuyun (Journal of Civil Engineering, 2024)
The durability of concrete is an essential factor in construction as a means to enhance the quality of public facilities planning. The durability of concrete structures can be degraded due to several factors, one of the factors is sulfate attack concrete. Expose to magnesium sulfate (MgSO4) causes more aggressive damage compared to sodium sulfate. The negative effect of sulfate exposure is the accelerated formation of microcracks that lead to concrete deterioration. This study aims to investigate the influence of expose to a 5% magnesium sulfate solution on the mechanical properties of Portland composite cement concrete (PCC). Sulfate exposure was conducted after the PCC concrete was cured in water for 28 days. Observations and testing were carried out in four stages: before exposure, after 28, 56, and 90 days. The compressive strength of the concrete increased by 8.78% after 56 days of exposure but decreased by 7.2% from the 56-day strength during the 90-day exposure. The modulus of elasticity, Poisson's ratio, tensile strength, and fracture energy were directly proportional to the compressive strength values generated during sulfate exposure. Additionally, the mass of the concrete increased by 0.87% after 56 days of exposure and then decreased to 0.56% during the 90-day exposure.